Cold tolerance of terrestrial isopod - Součková, Kateřina (Jihočeská univerzita, 2008)
The woodlice, Porcellio scaber (Latreille, 1804), is a terrestrial isopod. Its metabolic reserves and body size are important factors affecting the fitness attributes, such as survival at unfavourable conditions. The larger and heavier individuals did not survive longer than smaller individuals. Amount of glycogen and body weight (fresh and dry) appeared to be an inapplicable parameter in the observed differences among individuals during survival at low temperature. We compared three treatments (long day, short day, natural autumn conditions) of Porcellio scaber and found differences in amount of energy reserves and cryoprotectants.
Cold tolerance of terrestrial isopod
Keywords: body size; energy reserves; isopod; low temperature; body size; energy reserves; isopod; low temperature